The striped field mouse (Apodemus agrarius) as a host of fleas (Siphonaptera) and tapeworms (Cestoda) in suburban environment of Lublin (eastern Poland) - Zając, Zbigniew; Kulisz, Joanna; Woźniak, Aneta (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2019)
The striped field mouse, Apodemus agrarius, is one of the most abundant species among small rodents in Poland. It occurs commonly across the whole country inhabiting diverse ecological niches as meadows, farmlands, enclaves of natural habitats in cities. Wide range of ecological tolerance of this species makes it often the host, reservoir and vector of many pathogens: viruses, bacteria, protozoa, helminths and arthropods. The aim of the present study was to carry out a qualitative and quantitative analysis of the fleas community and intestinal tapeworms of A. agrarius in suburban environment of Lublin (eastern Poland). In studied population three species of Siphonaptera class i.e. Ctenophthalmus agyrtes, Nosopsyllus fasciatus, Hystrichopsylla talpae and one intestine Cestoda species Hymenolepis diminuta were identified. The results of our researches confirmed role of A. agrarius as the reservoir for tapeworms and host for fleas in urban environment. High level of the prevalence of fleas and tapeworms in rodents indicates the significant degree of contamination and can cause an epidemiological threat for human’s health.